PENGARUH ANIMASI TERHADAP REALISME DAN DAYA TARIK VISUAL GAME - Gunawan, I Putu Rezza Sastra (Anima Rupa, 2025)
In contemporary Game Development, animation plays a significant role in Improving the quality of graphics and visual experience of players. This article discusses how animation can increase realism, movement dynamics and also game interactivity. In this research, we analyze case studies of several games that are popular among today's young people that have undergone significant graphic changes using advanced animation techniques such as smooth motion capture, procedural animation, and visual effects that are pleasing to the eye. The analysis results show that animation strengthens the narrative and gameplay in addition to beautifying the visual appearance of the game, animation plays an important role in making the gaming experience more enjoyable. Player satisfaction and the commercial success of the game are directly influenced by animation.